1968
DOI: 10.1111/j.1749-6632.1968.tb19062.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrichosis Lanuginosa Associated With Diazoxide Therapy in Prepubertal Children: A Clinicopathologic Study*

Abstract: In 1963, Okun and coworkers' reviewed their 30 cases in which diazoxide had been used as an antihypertensive agent, and noted that hypertrichosis had occurred in six female patients. Hyperglycemia had occurred in 15 of the 30 patients and in 5 of the 6 patients who demonstrated "hirsutism". The hypertrichosis** appeared to be drug-dependent, and disappeared several weeks after the drug was discontinued.' The overall incidence of hypertrichosis during the field trials of diazoxide as an antihypertensive drug ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…A number o f potassium channel openers (PCOs), including diazoxide, minoxidil and pinacidil, have been shown to stimulate hair growth in man and monkeys [1][2][3][4], We have recently shown that these structurally unre lated P C O s stimulate the proliferation of mouse epidermal kératinocytes in primary culture [5], extending previous findings of minoxidil effects on mouse [6] and human [7] kératinocytes. In addition, a number o f P C O s, including diazoxide, have been shown to stimulate proliferation o f mouse hair follicle cultures [ In the present study we have used the cal cium indicator dye fura-2 to show that diazoxide induces both a transient and a sustained increase in Caj, as a result of increased calcium influx.…”
Section: Introductionsupporting
confidence: 70%
“…A number o f potassium channel openers (PCOs), including diazoxide, minoxidil and pinacidil, have been shown to stimulate hair growth in man and monkeys [1][2][3][4], We have recently shown that these structurally unre lated P C O s stimulate the proliferation of mouse epidermal kératinocytes in primary culture [5], extending previous findings of minoxidil effects on mouse [6] and human [7] kératinocytes. In addition, a number o f P C O s, including diazoxide, have been shown to stimulate proliferation o f mouse hair follicle cultures [ In the present study we have used the cal cium indicator dye fura-2 to show that diazoxide induces both a transient and a sustained increase in Caj, as a result of increased calcium influx.…”
Section: Introductionsupporting
confidence: 70%
“…The stronger response to minoxidil than diazoxide by deer follicles also reflects human hair growth in vivo, since hypertrichosis in adults treated with oral minoxidil is much more frequent than with oral diazoxide (Koblenzer and Baker, 1968;Burton and Marshall, 1979;Zins, 1988). Topical minoxidil also appears to be slightly more effective than diazoxide (Olsen et al, 1985;Olsen and Weiner, 1987;Roenigk, 1988).…”
Section: Figurementioning
confidence: 88%
“…Minoxidil, diazoxide, and pinacidil are all drugs that stimulate human hair growth, although none were designed to do so (Koblenzer and Baker, 1968;Burton et al, 1975;Burton and Marshall, 1979;Goldberg, 1988;Price et al, 1999). Minoxidil, currently the main topical treatment for hair loss (Olsen et al, 2002;Dawber and Rundegren, 2003), was originally developed as an anti-hypertension therapy.…”
mentioning
confidence: 99%
“…Diazoxide is another antihypertensive potassium channel opener which increases blood flow and is reputed to increase hair growth. 14,15 Laser Doppler velocimetry studies showed an increase in cutaneous blood flow after applying 1%, 3%, and 5% minoxidil solutions to the scalps of 16 balding men. 16 All three groups showed increases compared to a control group, and the 5% group showed the greatest increase.…”
Section: Mechanism Of Actionmentioning
confidence: 98%